The impact of social media on english proficiency among politeknik hulu Terengganu students - Hazian Ismail; Norkatyniy Ismail; Aida Fazlin Hisham (Global Econedu, 2024)
In today's digital era, social media is important in everyone's daily life, including students at tertiary level. Social media platforms such as Facebook, Instagram, Twitter, and YouTube are not just for socializing and entertainment but also serve as important tools for communication and education. The extensive use of social media offers a special chance to explore how it affects different areas of students' lives, such as their academic success and language abilities. This study aims to investigate the impact of social media on the English language proficiency of students at Politeknik Hulu Terengganu. A series of surveys were utilized to gather information from 76 participants enrolled in the Communicative English 3 course (DUE50032) during their last year of study. The information was examined with the help of SPSS version 20.0. The results showed that a majority of participants acknowledged the impact of social media on their English skills, particularly in writing, reading, listening, and speaking, with an average rating of 3.5. It concluded that students have positive views on the impact of social media activities, as well as perceiving social media as a constructive learning tool, that led to positive influence of social media engagement on their English proficiency.